The Impact of Game-Based Learning on Cognitive and Affective Outcomes in Science Education: A Systematic Review - Ilham Ramdhani; Achmad Samsudin; Duden Saepuzaman; Risnatati Risnatati; Muhammad Musyadad (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2026)
The aim of this study is to examine the application of game-based learning (GBL) in general science (IPA) and physics learning at all levels of education and its influence on students' abilities and affective. Systematic Literature Review (SLR) was conducted by analyzing 45 articles published over the last five years, focusing on educational level, game type and subject matter and its impact on the learning process. The research found that found that GBL approach is effective in developing students' abilities such as problem-solving, conceptual understanding, retention, and improving academic achievement. In the affective domain, it can increase students' motivation, engagement, and self-efficacy. In addition, the author highlights the existence of research that combines GBL with local culture, namely in research, besides being effective in increasing students' abilities and affective (motivation and involvement), it also introduces and re-popularizes local cultural values. This study recommends that schools and educational policymakers seriously consider the integration of game-based learning (GBL) by ensuring that the learning environment, media, and pedagogical practices are designed to support interactive, student-centered learning and training is needed for teachers can design well-directed learning and achieve learning objectives, especially in science lessons